Glucocorticoid-Induced Leucine Zipper as a Druggable Target in Inflammatory Bowel Diseases. Issue 7 (21st January 2020) - Ronchetti, Simona; Gentili, Marco; Ricci, Erika; Migliorati, Graziella; Riccardi, Carlo
Abstract: Inflammatory bowel diseases (IBDs) are chronic inflammatory disorders with a complex pathogenesis, affecting people of all ages. They are characterized by alternating phases of clinical relapse and remission, depending on the fine balance between immune cells and the gut microbiota. The cross talk between cells of the immune system and the gut microbiota can result in either tolerance or inflammation, according to multifactorial triggers, ranging from environmental factors to genetic susceptibility. Glucocorticoid (GC) administration remains the first-line treatment for IBDs, although long-term use is limited by development of serious adverse effects. Recently, new alternative pharmacological therapies have been developed, although these are not always effective in IBD patients. There is a constant demand for effective new drug targets to guarantee total remission and improve the quality of life for IBD patients. The glucocorticoid-induced leucine zipper (GILZ) has been implicated as a promising candidate for this purpose, in view of its powerful anti-inflammatory effects that mimic those of GCs while avoiding their unwanted adverse reactions. Here we present and discuss the latest findings about the involvement of GILZ in IBDs. Abstract : The glucocorticoid-induced leucine zipper (GILZ) has been implicated as a promising candidate for treatment of IBDs. This review summarizes what is known about the powerful anti-inflammatory effect of GILZ and its role in IBDs.